Patterns of consumption of dairy products in West Africa - Seyoum, Solomon (International Livestock Centre for Africa, 1988)
Looks into the patterns of consumption of dairy products in West Africa. Discusses trends in production, imports. Examines factors influencing dairy consumption patterns, particularly population growth, urbanization, incomes, consumer preferences and prices.